DAYA HAMBAT DAUN MANUKAN (RHINACANTHUS NASUTUS (L) KURZ) TERHADAP BAKTERI STAPHYLOCOCCUS AUREUS SECARA IN VITRO - Sunarti, Sunarti; Paninsari, Debora (Universitas Medan Area, 2020)
The use of antimicrobial such as antibiotics against infectious diseases with no control is quite common in Indonesia. This leads to increase morbidity and incidence of drug resistance. Staphylococcus aureus is a pathogenic bacteria, particularly infects the skin. The resistance it difficult to determine which antimicrobials were suitable for therapy. Manukan leaves have an active substance Rhinacanthin can be used as an anti-bacterial. The aim of this study was to determine the inhibition of ethanol extract of manukan leaves (Rhinacanthus nasutus (L) Kurz) against gram-positive bacteria (Staphylococcus aureus) in vitro with the extract concentration of 15, 30, and 60% as a control. This study was a true experiment through the in vitro test with the Kirby Bauer method. The results showed that the average diameter of the inhibition zone was at an extract concentration of 15, 30, and 60% are 9.97 mm, 10.95mm, and 13.18 mm. The Kruskal-Wallis test results showed a significant difference between the four treatment groups (p= 0.010). The Mann-Whitney test showed significant differences in the inhibition zone between control and treatment at 15, 30 and 60% (p= 0.037). In conclusion leave ethanol extract of manukan has antimicrobial activitiy in inhibiting staphylococcus aureus.